تجلّيات الجمال الخَلقي للنبي ﷺ في مرآة النور الإلهي (دراسة موضوعية فنية في ضوء القرآن الكريم والحديث الشريف): Manifestations of the Prophet’s ﷺ Physical Beauty in the Mirror of Divine Light) An Objective and Artistic Study in the Light of the Qur'an and Authentic Hadith ( (Al-Aasar, 2025)
This study explores the topic of “Manifestations of the Prophet’s ﷺ Physical Beauty in the Mirror of Divine Light” through an objective, rhetorical, and artistic lens. It brings together insights from the Qur’an, Prophetic traditions, and Sufi interpretations to reveal the outward beauty of the Prophet Muhammad ﷺ as a manifestation of divine illumination. The paper discusses how the Qur’an describes the Prophet ﷺ as a light and a luminous lamp, and how hadith literature links this divine light to his physical beauty. The study examines detailed descriptions of his noble features as recorded in classical works of al-shamāʾil al-nabawiyya—including his face, eyes, hair, gait, fragrance, voice, and smile—demonstrating how these aspects reflected his noble character, as indicated in the Qur’anic verse: “And indeed, you are of a great moral character” (Qur’an 68:4). Within a Sufi framework, the Prophet’s beauty is not perceived as mere appearance, but as a bridge to spiritual witnessing (shuhūd), where his light becomes a path of connection between the earthly realm and divine truth. The study concludes that the physical and moral beauty of the Prophet ﷺ formed a perfect harmony, embodying the ideal of the complete human being and the highest Prophetic station in which divine mercy, beauty, and truth are manifested.